A Phase II Trial of Cabozantinib in Hormone Receptor‐Positive Breast Cancer with Bone Metastases. (18th June 2020) - Xu, Jing; Higgins, Michaela J.; Tolaney, Sara M.; Come, Steven E.; Smith, Matthew R.; Fornier, Monica; Mahmood, Umar; Baselga, Jose; Yeap, Beow Y.; Chabner, Bruce A.; Isakoff, Steven J.
Abstract: Background: We assessed the antitumor activity of cabozantinib, a potent multireceptor oral tyrosine kinase inhibitor, in patients with hormone receptor‐positive breast cancer with bone metastases. Patients and Methods: In this single‐arm multicenter phase II study, patients received an initial starting dose of 100 mg, later reduced to 60 mg, per day. The primary endpoint was the bone scan response rate. Secondary endpoints included objective response rate by RECIST, progression‐free survival (PFS), and overall survival (OS). Results: Of 52 women enrolled, 20 (38%) experienced a partial response on bone scan and 6 (12%) had stable disease. Prior to the first repeat bone scan at 12 weeks, 19 (35%) patients discontinued study treatment because of early clinical progression or unacceptable toxicity. RECIST evaluation based on best overall response by computed tomography revealed stable disease in extraosseous tissues in 26 patients (50%) but no complete or partial responses. In 25 patients with disease control on bone scan at 12 weeks, only 3 (12%) patients developed extraosseous progression. The median PFS was 4.3 months, and median OS was 19.6 months. The most common grade 3 or 4 toxicities were hypertension (10%), anorexia (6%), diarrhea (6%), fatigue (4%), and hypophosphatemia (4%). Conclusion: Bone scans improved in 38% of patients with metastatic hormone receptor‐positive breast cancer and remained stable in an additional 12% for a minimum duration of 12 weeks on cabozantinib. Further investigations should assess the activity of cabozantinib in combination with other hormonal and other breast cancer therapies and determine whether bone scan responses correlate with meaningful antitumor effects. ClinicalTrials.gov   identifier . NCT01441947 Implications for Practice: Most patients with metastatic hormone receptor‐positive (HR+) breast cancer have bone involvement, and many have bone‐only disease, which is difficult to evaluate for response. This phase II single‐arm study evaluated the clinical activity of the small molecule MET/RET/VEGFR2 inhibitor cabozantinib in patients with metastatic HR+ breast cancer with bone metastases. This study met its primary endpoint, and cabozantinib treatment resulted in a significant bone scan response rate correlating with improved survival. This is the first study to use bone scan response as a primary endpoint in breast cancer. The results support further study of cabozantinib in HR+ breast cancer. Abstract : This article reports the results of a phase II trial of cabozantinib in women with metastatic hormone‐receptor‐positive (HR+) breast cancer with bone metastases, evaluating the bone scan response to cabozantinib in patients with metastatic breast cancer and whether bone scan response is a reliable surrogate primary endpoint for determining clinical benefit.